The racial democracy in the thought of Guerreiro Ramos: a balance of commentators - Caldas, Alan (2021)
The objective of this article is to carry out a critical assessment of the interpretations about the meaning, place, and function of the concept of racial democracy in the thinking of sociologist Alberto Guerreiro Ramos. Based on the critical survey of commentators (Marcos Chor Maio, Antonio Sérgio Alfredo Guimarães, Muryatan Santana Barbosa and Luiz Augusto Campos), we intend to show that the concept of racial democracy was appropriated, by the militant black intellectuals of the 1940s and 1950s, of academic intellectuality and transformed into a) a political and social project to integrate black populations into the emergent competitive social structure; and b) in treatment of colonized subjectivities based on the aesthetics of blackness. Finally, we will summarize the continuities and ruptures between racial democracy according to its traditional interpreters and according to the black militants of the 1940s and 1950s, especially Guerreiro Ramos.